Blue Creek Farm: a Matty Trescott novel - Thomas, Carroll (Hanover, NH Smith and Kraus, Inc., 2001)
In the late 1850s, with her mother dead and her brother riding for the Pony Express, Matty often finds that she must face all the dangers of pre-Civil War Kansas alone on the family farm. Prequel to: Matty's War
Keywords: Kansas - History - 1854-1861 - Fiction